Pemasaran Pariwisata Berbasis Edukasi Kota Malang - Safitri, Rini (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2020)
This study describes the historical phenomenon of Malang Brawijaya Museum.This study uses a qualitative literature method. The research setting is in MalangBrawijaya Museum. Data collection was obtained from written and electronicdocumentation and written sources.The result show what is meant by educational which is important for thecommunity of young generation or millennial generation so that they can have victoryvalues for the nation.Limitation / Implications for research are the need to develop promotion on socialmedia so that it is widely known by the public, both nationally and internationally.